Validation of 8th Class Science Achievement Test in District Sargodha - Naqeeb ul Khalil Shaheen, Muhammad; Shah, Nazir Haider; Sardar, Rukhsana (JSE, 2023)
This paper presents evidence for the validation of an Achievement Test of 8th class Science. A teacher-made test was used consisting of 30 multiple choice items from the 8th grade science curriculum. The test was applied to 150 sample students selected by random sampling technique. The test was analyzed by using three techniques for validating the test, these were, individual item’s difficulty level technique, technique of discrimination power of the items and distractor analysis technique. The study concluded that twelve items of the test were good and these items can be included in the next test, while, six items of the test were hard and needed to be improved. In addition to this, twelve items of the test needed revision. The study recommended that the teacher should be provided with advance special training in test construction. Furthermore, to make the process of item analysis easy and efficient, a computerized testing system is required to be established.